Large number of rebounding/founder HIV variants emerge from multifocal infection in lymphatic tissues after treatment interruption - Rothenberger, Meghan K.; Keele, Brandon F.; Wietgrefe, Stephen W.; Fletcher, Courtney V.; Beilman, Gregory J.; Chipman, Jeffrey G.; Khoruts, Alexander; Estes, Jacob D.; Anderson, Jodi; Callisto, Samuel P.; Schmidt, Thomas E.; Thorkelson, Ann; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2015)
Antiretroviral therapy (ART) suppresses HIV replication in most individuals but cannot eradicate latently infected cells established before ART was initiated. Thus, infection rebounds when treatment is interrupted by reactivation of virus production from this reservoir. Currently, one or a few latently infected resting memory CD4 T cells are thought be the principal source of recrudescent infection, but this estimate is based on peripheral blood rather than lymphoid tissues (LTs), the principal sites of virus production and persistence before initiating ART. We, therefore, examined lymph node (LN) and gut-associated lymphoid tissue (GALT) biopsies from fully suppressed subjects, interrupted therapy, monitored plasma viral load (pVL), and repeated biopsies on 12 individuals as soon as pVL became detectable. Isolated HIV RNApositive (vRNA+) cells were detected by in situ hybridization in LTs obtained before interruption in several patients. After interruption, multiple foci of vRNA+ cells were detected in 6 of 12 individuals as soon as pVL was measureable and in some subjects, in more than one anatomic site. Minimal estimates of the number of rebounding/founder (R/F) variants were determined by singlegene amplification and sequencing of viral RNA or DNA from peripheral blood mononuclear cells and plasma obtained at or just before viral recrudescence. Sequence analysis revealed a large number of R/F viruses representing recrudescent viremia from multiple sources. Together, these findings are consistent with the origins of recrudescent infection by reactivation from many latently infected cells at multiple sites. The inferred large pool of cells and sites to rekindle recrudescent infection highlights the challenges in eradicating HIV.
CRIS-Team Scopus Importer:2024-09-09
Keywords: Founder population; HIV/AIDS; Treatment interruption; Viral recrudescence